2019
DOI: 10.2478/hukin-2019-0024
|View full text |Cite
|
Sign up to set email alerts
|

Less Than One Millimeter Under the Great Toe is Enough to Change Balance Ability in Elite Women Handball Players

Abstract: Team handball is a complex intermittent sport game, which requires several motor abilities and effective postural control. Objective evaluation of stabilometric variables may be interesting to assess and improve functional parameters by postural control management. The purpose of the study was to evaluate the effects of a small additional thickness placed under the great toe (TUGT) on the Centre of Pressure (CoP) parameters in elite women handball players. Fourteen elite women handball players voluntarily part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 58 publications
2
3
0
Order By: Relevance
“…Our results suggest that a very small additional thickness is sufficient to change CoP measures. These postural reactions are consistent with previous reports that used mechanical stimulation of the plantar sole (Viseux et al 2018(Viseux et al , 2019b to promote cutaneous sensory facilitation, and could assist in changing the balance ability in patients with FM.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our results suggest that a very small additional thickness is sufficient to change CoP measures. These postural reactions are consistent with previous reports that used mechanical stimulation of the plantar sole (Viseux et al 2018(Viseux et al , 2019b to promote cutaneous sensory facilitation, and could assist in changing the balance ability in patients with FM.…”
Section: Discussionsupporting
confidence: 91%
“…Light-touch from the great toe allowed the activation of this cutaneous mechanoreceptors, and induced by low additional thickness, (i) provided significant no painfully somatosensory cues and (ii) induce attenuated postural sway. Compared to the no touch condition, an additional sensory stimulus stemming from lighttouch would lead to a stabilising effect on postural sway (Viseux et al 2018(Viseux et al , 2019b. Our results suggested that cutaneous mechanoreceptors of the great toe, especially the most superficial ones (Macefield et al 1990;Inglis et al 2002) were activated by the lowest additional thickness and seem to be consistent with sensory hypothesis and earliest reports using light-touch, which showed an improvement in postural performance (Jeka and Lackner 1994).…”
Section: Clinical Interestsupporting
confidence: 84%
See 2 more Smart Citations
“…Others have recently confirmed that mechanical facilitation of sensation of the plantar soles enhances postural stability. 93,94 A small raised edge placed underneath the boundary of the foot was shown to improve the reaction to unpredictable postural perturbations. 95 Changing the texture of a shoe-insert from smooth to clearly perceptible textured material can alter lower leg muscle activity during walking, suggesting that the sensory feedback from cutaneous receptors of the plantar surface of the foot improves dynamic balance control.…”
Section: Enhanced Cutaneous Information From the Foot Solementioning
confidence: 99%